Practice of Islam in America: An Introduction - Edward E. Curtis (NYU Press, 2017)
Muslims have always been part of the United States, but very little is known about how Muslim Americans practice their religion. How do they pray? What’s it like to go on pilgrimage to Mecca? What rituals accompany the birth of a child, a wedding, or the death of a loved one? What holidays do Muslims celebrate and what charities do they support? How do they learn about the Qur’an?